Synthesis of Fluorescent Carbon Dots from Soybean Residuals Using Hydrothermal Method - Ayu, Dinda G.; Gea, Saharman; Andriayani, Andriayani; Goei, Ronn (Universitas Tadulako, 2023)
Soybean residuals are biowaste composed of carbon chains and amine groups bounded in peptide linkages. The component was identified through FTIR analysis which showed the vibration of the diamide bond (N=C=N) at wave number 2132cm-1. Owing to the existence of these components, soybean has the potential to be used as a precursor to synthesize carbon nano-material, such as Carbon Dots (C - Dots). In this study, the synthesis of C - Dots material from soybean residuals was carried out using the facile hydrothermal method at a temperature of 200 oC for 6 hours. Afterward, the as-synthesized C - Dots were analyzed for their optical property, structure, and morphology. Based on the analysis of the UV - Vis and photoluminescent spectra, C - Dots exhibited absorbance peaks of 292 nm and 301 nm in the UV light region, and fluorescence emission peaks of 468 nm, with blue luminescence characteristics. The observation was supported by the morphological analysis using the HR - TEM, C - Dots exist in a spherical shape with an average particle size of 3.467 nm and a lattice distance of 0.363 nm. Besides, the C - Dots exhibited a good quantum yield of 28.15 %. From the results of the analysis, it is known that the synthesis of C - Dots material has been successfully carried out with particle size < 10 nm.